2019
DOI: 10.1080/21691401.2019.1608215
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived ECM hydrogels and their use as 3D culture scaffold

Abstract: Adipose tissue has the therapeutic capacity in the form of a fat graft, for example, for treatment of irradiation-induced scars and difficult to heal dermal wounds. For large-scale clinical application, an offthe-shelf product is warranted. In recent years, ECM-derived hydrogels are postulated to harbour therapeutic capacity and might even replicate the beneficial effects of adipose tissue. In normal homeostasis, the natural ECM acts as a deposit of growth factors, that releases them over time. In the healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Of these different forms, the gel has the potential to be created into a three-dimensional (3D) scaffold, while it can also be directly injected to the injury site for cell culture and tissue engineering applications [ 5 ]. These tissue-derived ECM gels are fabricated from different tissues such as porcine small intestine submucosa (SIS) [ 6 ], porcine urinary bladder [ 7 ], liver [ 8 ], brain [ 9 ], meniscus [ 10 ], human pancreas [ 11 ], tendon [ 12 ], and adipose tissue [ 13 ]. The development of ECM gel is associated with ECM solubilization by enzymatic (pepsin) digestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these different forms, the gel has the potential to be created into a three-dimensional (3D) scaffold, while it can also be directly injected to the injury site for cell culture and tissue engineering applications [ 5 ]. These tissue-derived ECM gels are fabricated from different tissues such as porcine small intestine submucosa (SIS) [ 6 ], porcine urinary bladder [ 7 ], liver [ 8 ], brain [ 9 ], meniscus [ 10 ], human pancreas [ 11 ], tendon [ 12 ], and adipose tissue [ 13 ]. The development of ECM gel is associated with ECM solubilization by enzymatic (pepsin) digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The development of ECM gel is associated with ECM solubilization by enzymatic (pepsin) digestion. Pepsin digests ECM into several incompletely digested proteins, proteoglycans, growth factors, and matricellular proteins, including collagens, elastin, laminin, fibronectin, hyaluronan, heparan, basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), transforming growth factor (TGF)-β, tenascin, osteopontin, and thrombospondin [ 5 , 7 , 10 , 13 ]. Among them, a major component of ECM is collagen, which is involved in processes of cell growth, proliferation, migration, and differentiation through inducing cell signalization.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are an ideal choice for 3D printing owing to their special chemical and physical properties and extrudability (Dong, Wang, Zhao, Zhu, & Yu, 2017). Hydrogel scaffolds can be used as cell scaffolds or slow‐release carriers because of (a) a bionic structure similar to that of the extracellular matrix, (b) their 3D network construction, cell migration, and growth‐promoting properties, particularly in drug delivery and tissue regeneration (Getova, van Dongen, Brouwer, & Harmsen, 2019; Zhang et al, 2019). Studies have demonstrated that sodium alginate (SA) can steady the matrix scaffold like a biological chain and guide cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the role of the ECM is essential for a tissue because it can maintain the homeostasis and it can influence many processes, such as the regulation of angiogenesis and cell adhesion. For this reason, the goal of the decellularization consists in achieving sufficient cells and nucleic acids removal from the source tissue while preserving the ECM structure and composition [ 67 , 68 ].…”
Section: Angiogenic Potential In Natural Hydrogelsmentioning
confidence: 99%
“…Indeed, in comparison to the other types of hydrogels, this one also manages to keep the physiological ratio between all the ECM components. Moreover, these hydrogels are used as a 3D culturing model that allow the cell adhesion, becoming a better system to simulate a real tissue [ 68 ]. Additionally, Wassenaar et al suggest the effect of the ECM hydrogel in the blood vessel formation and the macrophages’ attraction through endothelial progenitor cells recruitment [ 75 ].…”
Section: Angiogenic Potential In Natural Hydrogelsmentioning
confidence: 99%